Consequences of 'conversations not had': insights into failures in communication affecting delays in hospital discharge for older people living with frailty. Issue 4 (October 2020) - Redwood, Sabi; Simmonds, Bethany; Fox, Fiona; Shaw, Alison; Neubauer, Kyra; Purdy, Sarah; Baxter, Helen
Objectives: Older people living with frailty (OPLWF) are often unable to leave hospital even if they no longer need acute care. The aim of this study was to elicit the views of health care professionals in England on the barriers to effective discharge of OPLWF. Methods: We conducted semi-structured interviews with hospital-based doctors and nurses with responsibility for discharging OPLWF from one large urban acute care hospital in England. The data were analysed using the constant comparative method. Results: We conducted interviews with 17 doctors (12 senior doctors or consultants and 5 doctors in training) and six senior nurses. Some of our findings reflect well-known barriers to hospital discharge including service fragmentation, requiring skilled coordination that was often not available due to high volumes of work, and poor communication between staff from different organizations. Participants' accounts also referred to less frequently documented factors that affect decision making and the organization of patient discharges. These raised uncomfortable emotions and tensions that were often ignored or avoided. One participant referred to 'conversations not had', or failures in communication, because difficult topics about resuscitation, escalation of treatment and end-of-life care for OPLWF were not addressed. Conclusions: The consequences of not initiating important conversations about decisions relating to the end of life are potentially far reaching not only regarding reduced efficiency due to delayed discharges but also for patients' quality of life and care. As the population of older people is rising, this becomes a key priority for all practitioners in health and social care. Evidence to support practitioners, OPLWF and their families is needed to ensure that these vital conversations take place so that care at the end of life is humane and compassionate.